Sub-diffractive axial focusing due to a photonic nanojet from sphere much larger than wavelength - Jayesh Goswami; Snigdhadev Chakraborty; Uma Shankar; Srestha Roy; Atanu Ghosh; Krishna Kumari Swain; Basudev Roy (JPhys Photonics)
Photonic nanojets are known to focus the light smaller than the diffraction limit in the direction transverse to the propagation of the trapping beam (Lu et al 2021 Small 17 2006764), particularly when the diameter of the particle generating the nanojet is comparable to the wavelength of the light. However, the axial direction was not explored earlier. We show that when the diameter of the particle generating the nanojet is much larger than the wavelength of light, the light experiences focusing to a sub-diffractive spot in the axial direction, but the transverse direction is unaffected. we show an enhancement in the axial optical trap stiffness by a factor of 3 in the nanojet. We also show that the rotation rate of a spinning upconverting particle gets enhanced in the nanojet by about a factor of 3 as well. This would indicate focusing to a spot about 3 times smaller that the diffraction limit in the axial direction of the nanojet.